Yeasts of Pichia (Pichiaceae) dominate the mycobiome of Hermetia illucens (Diptera: Stratiomyidae) larvae during urban composting - Vallejo-Arróliga, Mónica; Rojas-Jimenez, Keilor (Revista de Biología Tropical, 2024)
Introduction: Hermetia illucens is a fly found worldwide in tropical and temperate regions that feeds on decaying organic matter in its larval stage, which makes them useful to accelerate composing processes. Bacterial component on the larval guts that helps to degrade organic matter is well studied, however fungal communities information is more scarse, specially in tropical regions. Objective: To determine fungal communities in the gut of H. illucens larvae naturally occurring during urban composting processes in a tropical region. Methods: ITS sequencing was employed to characterize fungal communities present in H. illucens larval gut. Results: The analysis of amplicon sequence variants (ASVs) unveiled a notable dominance of Saccharomycetales, being yeasts of the genus Pichia the most abundant. Other relatively abundant yeasts were Candida and Galactomyces and the genus Archaeospora from Archaeosporales. The last two groups not being reported in H. illucens before. Conclusions: Yeasts of the genus Pichia are the most abundant group, this result is in concordance with previous studies which suggest a stable insect-yeast relation. The description of previously unreported fungal groups highlights the importance of continuing to explore the mycobiome dynamics of this larva. This study offers insight into the mycobiome of naturally occurring H. illucens larvae in a tropical region.